Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 6 - Section 6.6 - Solving Quadratic Equations by Factoring - Exercise Set: 48


The solutions are -13 and 2.

Work Step by Step

$x^{2}$-26=-11x $x^{2}$-26+11x=-11x+11x $x^{2}$-26+11x=0 $x^{2}$+13x-2x-26=0 x(x+13)-2(x+13)=0 (x-2)(x+13)=0 x-2=0 or x+13=0 x-2+2=0+2 or x+13-13=0-13 x=2 or x=-13 The solutions are -13 and 2. Chec Let x=-13 $x^{2}$-26=-11x $(-13)^{2}$-26=-11(-13) 169-26=143 143=143 Let x=2 $x^{2}$-26=-11x $2^{2}$-26=-11*2 4-26=-22 -22=-22
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.